IDIOMETRIC ASSAY, THE 3RD WAY - A NONCOMPETITIVE IMMUNOASSAY FOR SMALL MOLECULES - BARNARD, G; KARSILIYAN, H; KOHEN, F (MOSBY-ELSEVIER, 1991)
A novel, noncompetitive immunoassay applicable to the measurement of small molecules including ovarian steroids is described. Using monoclonal antibodies with the ability to recognize both beta-typic and alpha-typic binding sites, a new simplified, sensitive, and specific immunoassay system has been developed. The initial work of this development is presented, along with preliminary results for a novel immunoassay for estradiol.
Keywords: OVARIAN STEROIDS; NONCOMPETITIVE IMMUNOASSAY; MONOCLONAL ANTIBODIES; ESTRADIOL; Obstetrics & Gynecology